Memory and aging (Alzheimer's Association, 1993)
An Alzheimer's Association pamphlet on the Alzheimer's Disease. Intended for the general public.
Keywords: Dementia; geriatrie; demence; Alzheimerova nemoc; senioři; Aged; Alzheimer Disease; neurologie